How Social Media and e-WOM Build Perlang Tourist Village’s Brand - Damayanti, Tissa Aulia; Pusparini, Marissa; Barasa, Robert Tua (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study examines the impact of social media quality and credibility on enhancing destination brand awareness through electronic word-of-mouth (e-WOM), utilizing Perlang Tourist Village in Bangka Belitung as a case study. Despite its national recognition, Perlang faces challenges in digital branding and infrastructure, necessitating strategic social media engagement to address these issues. Employing a quantitative explanatory design, data were collected from 307 respondents via purposive sampling and analyzed using PLS-SEM. The results show that both social media quality and credibility significantly influence destination brand awareness, with e-WOM serving as a key mediating variable. All seven hypotheses were supported, confirming the conceptual framework. The findings suggest that high-quality and credible content fosters trust, encourages user advocacy, and strengthens brand recognition. This research contributes to the theoretical understanding of digital branding in community-based tourism and offers practical implications for destination marketers seeking to optimize social media strategies.